Botrytis cinerea, new pathogen infecting oregano crops in Argentina - Caligiore Gei, Pablo Fernando; Piccolo, Ricardo Jose (2017)
In October 2013 plants necrotic leaves and cankers on the stems were observed in oregano crops (Origanum vulgare ssp. hirtum en Tres Esquinas (Mendoza, Argentina). To the best of our knowledge this is the first report of B. cinerea affecting oregano crops in Argentina.